2018
DOI: 10.1038/s41594-017-0020-6
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of AAUAAA polyadenylation signal recognition by the human CPSF complex

Abstract: Mammalian mRNA biogenesis requires specific recognition of a hexanucleotide AAUAAA motif in the polyadenylation signals (PAS) of precursor mRNA (pre-mRNA) transcripts by the cleavage and polyadenylation specificity factor (CPSF) complex. Here we present a 3.1-Å-resolution cryo-EM structure of a core CPSF module bound to the PAS hexamer motif. The structure reveals the molecular interactions responsible for base-specific recognition, providing a rationale for mechanistic differences between mammalian and yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 28 publications
9
144
0
Order By: Relevance
“…Among the protein complexes contributing to 3' processing of mammalian mRNA precursors, CstF and CF I have previously been reconstituted from recombinant proteins (Takagaki and Manley 1994;Rüegsegger et al 1998;Yang et al 2011;Yang et al 2018). Of the central factor, CPSF, only the mPSF subcomplex, active in polyadenylation, has been reconstituted (Schönemann et al 2014;Clerici et al 2017;Clerici et al 2018;Sun et al 2018), but the subunit composition of CPSF is reasonably clear from biochemical experiments (Bienroth et al 1991;Shi et al 2009;Schönemann et al 2014). In contrast, CF II had never been purified to the point that its subunit composition could be judged.…”
Section: Discussionmentioning
confidence: 99%
“…Among the protein complexes contributing to 3' processing of mammalian mRNA precursors, CstF and CF I have previously been reconstituted from recombinant proteins (Takagaki and Manley 1994;Rüegsegger et al 1998;Yang et al 2011;Yang et al 2018). Of the central factor, CPSF, only the mPSF subcomplex, active in polyadenylation, has been reconstituted (Schönemann et al 2014;Clerici et al 2017;Clerici et al 2018;Sun et al 2018), but the subunit composition of CPSF is reasonably clear from biochemical experiments (Bienroth et al 1991;Shi et al 2009;Schönemann et al 2014). In contrast, CF II had never been purified to the point that its subunit composition could be judged.…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently reported the structures of a quaternary complex of human CPSF-160, CPSF-30, WDR33 and an AAUAAA PAS RNA (Figs. 1A, 1B) (18,19), the structure of a ternary complex of the yeast protein homologs (Cft1, Yth1 and Pfs2, without RNA) (20), as well as the structure of a binary complex of human CPSF-160 and WDR33 (21). The structures of the quaternary complexes revealed extensive and specific interactions between the AAUAAA PAS and WDR33 and CPSF-30 ( Fig.…”
Section: Introductionmentioning
confidence: 94%
“…A U3-A6 Hoogsteen base pair was observed in the PAS when bound to the CPSF-160-WDR33-CPSF-30 ternary complex (Fig. 1C) (18,19). The binding mode of the PAS suggests that other Hoogsteen base pairs, such as C3-G6, could be accommodated, while a wobble U3-G6 base pair would not fit.…”
Section: Variation Of the U3-a6 Hoogsteen Base Pairmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of the S. cerevisiae complex demonstrated that CPF is organised into three functionally different, stably associated modules: poly(A) polymerase, nuclease, and phosphatase (Casañal et al, 2017). Reconstitution and structural analysis of the mammalian polymerase module (CPSF160-WDR33-CPSF30-Fip1) have revealed that the zinc finger domains 2 and 3 of CPSF30, as well as the WD40 domain and the N-terminal region of WDR33, interact with the PAS element (Clerici et al, 2017(Clerici et al, , 2018Schönemann et al, 2014;Sun et al, 2018). Although RNA is not present in the cryo-EM structure of the S. cerevisiae polymerase module, its overall organisation is very similar to the mammalian module (Casañal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%